Breaking the unbreakable: A paediatric case of dolutegravir resistance from KwaZulu-Natal - Sibongiseni Malinga; Aabida Khan; Moherndran Archary (AOSIS, 2023)
We report a case of dolutegravir resistance in KwaZulu-Natal in a 13-year-old male two years after starting dolutegravir. Resistance most likely developed due to poor adherence as a result of psychosocial issues. This case highlights the importance of the role of the family unit in impacting adherence and close monitoring of treatment-experienced patients with virologic failure following switching to dolutegravir-based regimens.